Analisis Kinerja Kincir Air Overshot dengan Penambahan Lubang pada Sudu - Adam Susanto; Atus Buku; Yusuf Siahaya (CV. IRA PUBLISHING, 2026)
This study aims to analyze the performance of an overshot water wheel with holes added to the blades, focusing on mechanical power, torque, and efficiency. The experiment was conducted using a laboratory-scale water wheel prototype with a fixed number of eight blades. The experimental variations included the number of holes in each blade (12, 16, and 20) and hole diameters (0.07 m, 0.09 m, and 0.11m), with a blade without holes used as a reference condition. The tests were carried out under relatively constant water flow conditions, with shaft rotational speed measured using a tachometer and torque obtained via a braking method. The results indicate that adding holes to the blades significantly improves the performance of the overshot water wheel. The optimal configuration was achieved with 20 holes and a hole diameter of 0.11 m, producing a maximum power of approximately 21 W, the highest torque, and a maximum efficiency of 7.9%. This study demonstrates that optimizing blade design by adding holes is an effective approach to enhancing the performance of overshot water wheels in small-scale microhydropower applications.